A New Approach for Nizhnik-Novikov-Veselov System - Demiray, Seyma Tuluce; Bulut, Hasan (Jomard Publishing, 2019)
Studies in recent years have examined the analytical solutions of nonlinear evolution equations (NLEEs). These equations are handled by using a lot of methods. Especially, hyperbolic function solutions, soliton solutions and others have been revealed for these NLEEs. A powerful technique is used to attain some exact solutions of Nizhnik-Novikov-Veselov (NNV) system. Hyperbolic function solutions and dark soliton solutions of this system are constructed via modified exp(??(?)) -expansion function method (MEFM). Then, results that we obtained are submitted. Moreover, we draw 2D and 3D surfaces of some analytical solutions that we procured with the help of this method. © 2019, Jomard Publishing. All rights reserved.
Keywords: Hyperbolic function solutions; modified exp(??(?)) - expansion function method; Nizhnik-Novikov-Veselov system; soliton solutions